Analisis Strategi Pengelolaan Keuangan Sekolah Berbasis Syariah Pada Muslimeen Suksa School, Thailand - Siti Maisyaro Nasution; Syahrul Amsari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Sharia financial management strategies play an important role in improving school financial management. This study aims to improve understanding of management functions, sharia principles and implementation of strategies in financial management of Muslimeen Suksa schools. This study uses a descriptive approach that is classified as a qualitative method by utilizing observation and interview data and additional information from journals, books and articles. The results of the study indicate that the school management function has been running well in financial planning and implementation, especially in providing educational services and prioritizing more important needs. While in terms of organization, it still needs improvement to be more effective and structured. Meanwhile, the supervision aspect requires community participation to monitor school financial management. Similarly, the sharia principles in school finance show that the principles of justice, effectiveness and efficiency have been implemented well. However, the principles of transparency and accountability in their application still need to be improved. Therefore, this study confirms that good school financial management must be in accordance with management functions and sharia principles.